A novel high temperature eutectic salt and its composite with enhanced high conductivity. (March 2023) - Kang, Zeyang; Huang, Sihan; Liu, Xiangyang; Zhang, Ying; He, Maogang
Abstract: Suitable eutectic point, high specific heat capacity, large latent heat, low cost and other factors were considered to design a new type of molten salt in this work, and composite phase change materials (CPCM) were prepared for the utilization of solar energy by thermal energy storage. The designed molten salt is NaF-Na2 CO3 -Na2 SO4 eutectic salt ( x NaF = 36.29 mol%, x Na2 CO3 = 29.93 mol% and x Na2 SO4 = 33.78 mol% with melting temperature of 936.1 K), high liquidus specific heat capacity (1.76 J·(g·K) −1 ) and high latent heat (342.9 J·g −1 ), expanded graphite (EG) is used for improving structural stability and thermal conductivity, and graphene nanoplatelets (GNPs) is used for further improvement on thermal conductivity. The thermophysical properties of base salt and the effects of EG and GNPs nanomaterials additives on the thermophysical properties of the composite were investigated, especially the greatly increased effect on thermal conductivity (1120 % enhancement for EG-PCM and 1109 % enhancement for EG-GNPs-PCM). The prepared NaF-Na2 CO3 -Na2 SO4 eutectic base salt and EG-PCM, EG-GNPs-PCM composites have a promising application prospect in the high-temperature energy storage. Highlights: An innovation molten salt with low cost and good capacities is successfully designed. Thermophysical properties of the salt and cpcm are determined experimentally. The associated effect of eg and gnps on the thermophysical properties are investigated. The thermal conductivity of cpcm can be greatly enhanced (1120 %).